PEJALAN KAKI DALAM PUISI “CATATAN SEORANG PEJALAN KAKI” KARYA TS. ATJAT DAN “PEJALAN KAKI” KARYA NOORAL BASO : SEBUAH ANALISIS DIKOTOMI PUISIPEJALAN KAKI DALAM PUISI “CATATAN SEORANG PEJALAN KAKI” KARYA TS. ATJAT DAN “PEJALAN KAKI” KARYA NOORAL BASO : SEBUAH ANALISIS DIKOTOMI PUISI - Dian Respati Pranawengtyas (Balai Bahasa Sulawesi Tengah, 2015)
Poems is the expression of the poets. The expression come from the poets’ daily life activities. Based on the facts, it is not impossible that there are similarities in the poems which are produced from different poets. Catatan Seorang Pejalan Kaki written by T.S. Atjat and Pejalan Kaki by Nooral Baso have similarities in the title. Finding the similarities and differences based on shapes and contents is the aim in this paper. The method of collecting data is library method and the analysis method is qualitative. The result shows that there are similarities and differences in the shape and content of those poems. The differences in the shape are dictionand rhyme while the similarities are figurative speech and imagery. The analysis of content shows that there is similarities between theme, message, and nuance.